Henoch-Schonlein purpura in child: a case report and review of the literature - Sonawane, Vijay B.; Kotrashetti, V. A.; Bainade, Kapil S.; Nair, Shweta; Yewale, Sushil (International Journal of Contemporary Pediatrics, 2020)
Henoch-Schonlein purpura (HSP) is the most common vasculitis of childhood and is characterized by leukocytoclastic vasculitis and immunoglobulin A deposition in the small vessels in the skin, joints, gastrointestinal tract and kidney. We report a 6 year old female child presented with rashes over both legs and buttocks along with joint pain and abdominal pain and multiple episodes of vomiting. Patient was diagnosed with HSP and treated with oral prednisolone followed by methylprednisolone and other supportive care.